MICROWAVE-ASSISTED EXTRACTION OF PHENOLIC COMPOUNDS FROM OLIVE LEAVES; A COMPARISON WITH MACERATION - Z. Rafiee; S. M. Jafari; M. Alami; M. Khomeiri (Journal of Animal and Plant Sciences, 2011)
The purpose of this study was to extract phenolic compounds from olive leaves of Koroneiki, Roghani and Mission varieties by maceration and Microwave-assisted extraction (MAE) methods with different solvents. Our results revealed that the extraction method, solvent and variety had a significant effect on the amount of phenolic compounds (p<0.05). In both extraction methods, Koroneiki and Mission varieties had the most and least phenolic contents, respectively. In terms of solvents applied, ethanol was the most effective one, producing the highest extraction yield and acetone had the lowest yield. Generally, the highest phenolic concentration was achieved at 24 h (69.027 mg TAE/ g) in maceration method and at the 15 min (88.298 mg TAE/ g) of exposure during MAE by ethanol extract of Koroneiki variety. Furthermore, we found that MAE had a higher extraction yield compared with the maceration method.
Keywords: olive leaf; phenolic; extraction; microwave; maceration